What's wrong with using steroids? Exploring whether and why people oppose the use of performance enhancing drugs. - Landy, Justin F.; Walco, Daniel K.
The use of performance enhancing drugs (PEDs) elicits widespread normative opposition, yet little research has investigated what underlies these judgments. We examine this question comprehensively, across 13 studies. We first test the hypothesis that opposition to PED use cannot be fully accounted for by considerations of fairness. We then test the influence of 10 other potential drivers of opposition in an exploratory manner. We find that health risks for the user and rules and laws prohibiting use of anabolic steroids reliably affect normative judgments. Next, we test whether these patterns generalize to a different PED-cognitive-enhancement drugs. Finally, we sketch a framework for understanding these results, borrowing from Social Domain Theory (e.g., Turiel, 1983). We argue that PED use exemplifies a class of violations with properties of moral, conventional, and prudential offenses. This research sheds light on a widespread, but understudied, normative judgment, and illustrates the utility of exploratory methods.
Keywords: Psychology -- Periodicals; Performance enhancing drugs; Normative judgment; Social domain; Exploratory methods